Natural Flavans and (Iso)Flavanones with Anticancer Activity: A Review - Gangopadhyay, Arindam (Current Organic Chemistry, 2021)
The present review describes 108 new examples of naturally occurring flavans and flavanones having cytotoxic potential, which have been reported during the period of 2005 to mid-2020. These compounds are found either as aglycones or as glycosides, comprising flavans, flavanones, isoflavanones and miscellaneous flavanones (homo- and bi-flavanones). The main topics addressed in this review are source, structure, and cytotoxic activity in detail and the structure-activity relationship.
Keywords: anticancer activity